APLIKASI ANALISIS FAKTOR KONFIRMATORI TERHADAP SIKAP KEBERAGAMAAN MAHASISWA - Rijal Firdaos (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The aim of this research is to develop an instrument of religious attitude for Islamicstudents higher education at Tarbiyah Faculty of IAIN Raden Intan Lampung. The population of this research is Islamic students of Tarbiyah Faculty amounted to 150 people. The method research used survey technique. The Parameter of this research used Thurstone scale or called with equal appearing interval. The empirical research results through has confirmed 27 items are consist in three dimension. The result by using factor analysis of confirmatory is indicating that all items indicator have factor loading more than 0.30, and support which has estimated with enough theory. Construct reliabilities by Alpha Cronbach indicate that instruments developed have fulfilled limit acceptance of reliabilities coefficient more than 0.70.